Access for Refugees Into Higher Education: A Review of Interventions in North America and Europe. (September 2019) - Streitwieser, Bernhard; Loo, Bryce; Ohorodnik, Mara; Jeong, Jisun
This paper examines current interventions to reduce barriers to access into higher education for refugees in North America and Europe. We analyze a diversity of interventions sponsored by host governments, higher education institutions, foundations, nongovernmental organizations, and individuals. These interventions differ in size, delivery method, focus, and extent of support, and range from a single language course or limited online learning opportunity to fully accredited higher education programs. However, significant problems hamper the efficacy of many current interventions. We examine providers' rationales for working with refugees using Knight and De Wit's rationales for internationalization of higher education, later reconceptualized in four interrelated groups of rationales: academic, political, economic, and socio-cultural. To these, we propose adding a fifth category: humanism. To widen refugee participation and success in higher education, we suggest that policy makers and administrators should adopt a longer-term perspective, increase transparency, and use evidence-based approaches to develop and evaluate refugee programming.